(3bQGAI aj GdNWGH GdEYdGei h GdSjGSj GdeYGUQ (B:s (3fXQjI fbOjI (B/s - (3MhGJ, eMeO Ydjs ((3GdbGgQI (B:s (3ecJHI eOHhdj ,s, 2005)
(3gPG GdcJGH jYJHQ GVGaI LOjOI h eVjFI GdQ GdGYeGd h GdHMhK aj eLGd GdOQGSGJ GdGYdGejI h SHH Pdc Gf GdcGJH GdJRe HGdeOGNd GdfbOjI aj eYGdLI GdehVhYGJ GdeNJdaI GdJj bOegG eeG jYO ejRI GSJKfGFjI JYdi ef GdbjeI GdYdejI h GdeYQajI dgPG GdYed MjK Gf GdGZdH GdGYe aj GdOQGSGJ GdJj JYGdL ehVhYGJ gPG GdcJGH JaJbQ Gdi GdefXhQ GdfbOj Hd jZdH YdjgG GdWGHY GdfXQjs
(3HHdjhZQGajG (B: (3U(B.358-362s
Keywords: (3GdEYdGe GdSjGSjs; (3GdYhdeIs; (3GdhWf GdYQHjs; (3EjQGfs